Variations in the Profiles of Vascular-Related Factors Among Different Sub-Types of Polycystic Ovarian Syndrome in Northern China - Liu, Mei-mei; Chen, Xiu-hui; Lu, Xiu-min; Wang, Fang-fang; Wang, Chao; Liu, Yu; Li, Pei-ling; Du, Bo-tao; Liang, Sha; Gong, Pi-dong; Wang, Yu-xin (Frontiers in Endocrinology, 2021)
Recently, a growing body of evidence has suggested that abnormal ovarian angiogenesis, secondary to the imbalance between various angiogenic markers, is involved in the pathogenesis of PCOS, and this has led to the use of various interventions (such as Diane-35) to restore the normal ovarian angiogenesis. Therefore, we conducted the current investigation to determine the role of such markers (endothelial growth factor (VEGF), endostatin (ES), and thrombospondin-1 (TSP-1)) in the pathogenesis of PCOS along with the associated changes in ovarian blood flow in patients with PCOS compared to healthy controls, both before and after a course of oral contraception. A total of 381 patients with PCOS and 98 healthy females of childbearing age were recruited from July 2014 to June 2017 at the Reproductive Center of the Second Affiliated Hospital of Harbin Medical University. The serum levels of VEGF, ES, and TSP-1 were determined by enzyme-linked immunosorbent assay, while ovarian perfusion was measured by the pulsatility index (PI) and resistance index (RI) by using transvaginal color Doppler ultrasound. Repeated analyses were carried out after 3 months of Diane-35 treatment. Post-treatment serum levels of luteinizing hormone (LH)/follicle stimulating hormone (FSH) ratio of patients with PCOS decreased significantly (P <0.05). The RI values of most PCOS patients increased after treatment (P<0.05), while PI was significantly increased in all patients (P<0.05). However, variable changes in the serum levels of TSP-1, VEGF, and ES after treatment were observed. Serum VEGF levels showed a negative correlation with serum LH/FSH ratio, T concentration, and ES (P <0.05), while ES levels were negatively correlated with serum T concentrations only (P<0.05). The markers of angiogenesis (VEGF, ES, and TSP-1) were expressed differently among PCOS patients, who also responded differently to the same course of Diane-35 treatment. This field still warrants further investigation to reach a more definitive conclusion.